Final answer:
To find the inverse of the function f(x) = 4x + 5, switch x and y in the equation, then solve for y to get the inverse function, which is f-1(x) = (x - 5) / 4.
Step-by-step explanation:
To find the inverse of the function f(x) = 4x + 5, you would follow these steps:
- Replace f(x) with y: y = 4x + 5.
- Switch the roles of x and y: x = 4y + 5.
- Solve the equation for y to find the inverse function:
- Subtract 5 from both sides: x - 5 = 4y.
- Divide by 4: y = (x - 5) / 4.
The inverse function is: f-1(x) = (x - 5) / 4.
This inverse function will satisfy the condition that f(f-1(x)) = x and f-1(f(x)) = x, which is the defining property of an inverse function.